Impact of Policy Environment Characteristics on Physical Activity and Sedentary Behaviors of Children Attending Afterschool Programs. (June 2013) - Beets, Michael W.; Huberty, Jennifer; Beighle, Aaron; Moore, Justin B.; Webster, Collin; Ajja, Rahma; Weaver, Glenn
State and national organizations recently developed policies focused on increasing physical activity (PA) in afterschool programs (ASPs). These policies emphasize "activity friendly" environment characteristics that, when present, should lead to higher levels of PA and reduce the amount of time children spend sedentary during an ASP. Currently, little is known about the impact of existing PA policies on children's PA and sedentary behaviors in ASPs. A sample of 18 community-based ASPs serving 1, 241 children (5-12 years) were audited for environment features outlined in existing PA policies (i.e., presence of a written policy to promote PA, collecting child feedback, staff training to promote PA and the quality of that training, holding parent workshops, use of PA curricula, evaluating PA, allocating time in the schedule for PA opportunities, and providing activities that appeal to both boys and girls). Children's PA and sedentary behavior were measured via accelerometry. Unexpectedly, the presence of a written policy, collecting child feedback, and receiving 1 to 4 hours of staff training for PA was associated with an increase in time spent sedentary and a decrease in PA. Conversely, allocating 50% or more time in an ASP schedule for PA and providing activities that appealed to boys and girls was associated with a decrease of time spent sedentary and an increase in PA. The present state of practice in ASPs suggests that policy environment characteristics are largely unrelated to the amount of PA children accumulate while attending ASPs.